(untitled) - Schnubel, Mark (Stamford, CA, 2015)
This edition now offers opportunities to explore the latest advancements in suspension and steering technology, including: run-flat tires, shock absorber mountings on SUVs, the effect of 42V electrical systems on power steering pumps, electronic power and four-wheel steering systems, and new wheel alignment procedures
Keywords: Ô tô,Ô tô,Automobiles,Automobiles; Nhún và hệ thống giảm xóc,Bảo trì và sửa chữa,Thiết bị lái,Bảo trì và sửa chữa,Springs and suspension,Maintenance and repair,Steering-gear,Maintenance and repair